2007
DOI: 10.1002/bies.20582
|View full text |Cite
|
Sign up to set email alerts
|

Mutational activation of ErbB family receptor tyrosine kinases: insights into mechanisms of signal transduction and tumorigenesis

Abstract: SummarySignaling by the Epidermal Growth Factor Receptor (EGFR) and related ErbB family receptor tyrosine kinases can be deregulated in human malignancies as the result of mutations in the genes that encode these receptors. The recent identification of EGFR mutations that correlate with sensitivity and resistance to EGFR tyrosine kinase inhibitors in lung and colon tumors has renewed interest in such activating mutations. Here we review current models for ligand stimulation of receptor dimerization and for act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
89
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(90 citation statements)
references
References 65 publications
0
89
0
1
Order By: Relevance
“…The closed conformation (inactive), has intramolecular interactions between subdomains II and IV Dawson et al, 2005;Riese et al, 2007]. 2.…”
Section: Erbb Receptors Homodimerization and Heterodimerizationmentioning
confidence: 99%
See 2 more Smart Citations
“…The closed conformation (inactive), has intramolecular interactions between subdomains II and IV Dawson et al, 2005;Riese et al, 2007]. 2.…”
Section: Erbb Receptors Homodimerization and Heterodimerizationmentioning
confidence: 99%
“…2. The open conformation (active), where subdomains I and III form a ligand-binding pocket that permits interactions between a single ligand and subdomains I and III Dawson et al, 2005;Riese et al, 2007]. In the absence of ligand binding, the extracellular region of EGFR, ErbB-3 and ErbB-4 has equilibrium between closed and open conformation Dawson et al, 2005;Ozcan et al, 2006;Riese et al, 2007].…”
Section: Erbb Receptors Homodimerization and Heterodimerizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The EGF receptor is linked to the generation and development of human cancer, and EGF antagonists have been used to develop effective cancer therapeutics (2,3). The interactions between receptor tyrosine kinases and adaptor proteins are crucial for the transduction of intracellular growth signals from the plasma membrane to the nucleus (4,5).…”
mentioning
confidence: 99%
“…14 While such mutations have been identified in 10-30% of non-small cell lung cancer, 19 this is a less frequently documented event in colorectal cancer. 20 The investigators found only two patients with EGFR mutations in the kinase region in their patient population.…”
mentioning
confidence: 99%